The Price of a CEO's Rolodex - Engelberg, Joseph; Gao, Pengjie; Parsons, Christopher A. (Review of Financial Studies, 2013)
CEOs with large networks earn more than those with small networks. An additional connection to an executive or director outside the firm increases compensation by about $17,000 on average, more so for "important" members, such as CEOs of big firms. Pay-for-connectivity is unrelated to several measures of corporate governance, evidence in favor of an efficient contracting explanation for CEO pay. © 2012 The Author.